If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(x+9)-4.25(-8x-16)=41
We simplify the equation to the form, which is simple to understand
-2(x+9)-4.25(-8x-16)=41
Reorder the terms in parentheses
+(-2x-18)-4.25*(-8x-16)=41
Remove unnecessary parentheses
-2x-18-4.25+*(-8x-16+)=+41
Reorder the terms in parentheses
-2x-18+(+34x+68)=41
Remove unnecessary parentheses
-2x-18+34x+68=+41
We move all terms containing x to the left and all other terms to the right.
-2x+34x=+41+18-68
We simplify left and right side of the equation.
+32x=-9
We divide both sides of the equation by 32 to get x.
x=-0.28125
| 0.09x+3.95=57.95 | | 10-(4z-4)=1-5z | | -1=x/6- | | 2x-8=4+3x | | 64=8a | | 15=y/5 | | fx=-3(3)-15 | | 5(v-2)-6=2(-8v+7)-3v | | (x-3/5+x)=10/14 | | -42.84b+8=5 | | 4x+5y=7fory | | 32t^4-162y^4=0 | | 2z-4=10 | | 3f+2+9=13+5f | | 10(6+2x)=-2(8x+6) | | (-4x^2)+(5y)-(-6x^2)-(7y)=x | | Hg(x)=3.08(138)sqrt+18.97 | | 9+-4=x | | f(-3)=3(-3)-15 | | ln(x^2+7x-31)=0 | | 6x^2-16x-360=0 | | 9(y+9)=6+8y | | 10x-5=0 | | 15-n=n+5 | | 2(p-1)=7p+3-4p | | 15-n=5+n | | 5X+2=3X-(8x+2) | | -6+(-4)=x | | 15+n=5+n | | 10+n=n+5 | | 3r+3=6r-1 | | -3+8h=-5 |